2021
DOI: 10.1021/acs.inorgchem.1c02606
|View full text |Cite
|
Sign up to set email alerts
|

Can a Nitrosyl of a Mn(II)–Porphyrin Complex Release Nitroxyl/HNO?

Abstract: In general, the nitrosyl complexes of Mn(II)−porphyrinate having the {Mn(NO)} 6 configuration are not considered as HNO or nitroxyl (NO − ) donors because of [Mn I −NO + ] nature. A nitrosyl complex of Mn(II)− porphyrin, [Mn(TMPP 2− )(NO)], 1 [TMPPH 2 = 5,10,15,20-tetrakis-4-methoxyphenylporphyrin], is shown to release HNO in the presence of HBF 4 . It is evidenced from the characteristic reaction of HNO with triphenylphosphine and isolation of the [(TMPP 2− )Mn III (H 2 O) 2 ](BF 4 ), 2. This is attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In the X-band EPR study of the reaction mixture at 77 K, the reaction mixture shows a sharp signal at g ∼ 2.04, which supports the formation of [Fe II (TPP)(NO)] in the reaction medium (Figure 3). 3,26,27 A similar reaction was observed with complex 1 in the presence of [Fe III (DTC) 3 ] without the addition of HBF 4 in a dry and degassed CH 2 Cl 2 medium. Upon addition, complex 1 was found to donate NO − to [Fe III (DTC) 3 ] to result in [Fe II (DTC) 2 (NO)].…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In the X-band EPR study of the reaction mixture at 77 K, the reaction mixture shows a sharp signal at g ∼ 2.04, which supports the formation of [Fe II (TPP)(NO)] in the reaction medium (Figure 3). 3,26,27 A similar reaction was observed with complex 1 in the presence of [Fe III (DTC) 3 ] without the addition of HBF 4 in a dry and degassed CH 2 Cl 2 medium. Upon addition, complex 1 was found to donate NO − to [Fe III (DTC) 3 ] to result in [Fe II (DTC) 2 (NO)].…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…This 1698 cm −1 stretching frequency is attributed to the nitrosyl stretching of newly formed [Fe II (TPP)-(NO)]. 3,14,26,27 The reaction was found to be completed in a near-quantitative manner. In the X-band EPR study of the reaction mixture at 77 K, the reaction mixture shows a sharp signal at g ∼ 2.04, which supports the formation of [Fe II (TPP)(NO)] in the reaction medium (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The optimized structures were not largely changed by the functional, except the Mn–OH 2 distance in 3 . The calculated Mn–OH 2 distances (2.50–2.76 Å) in 3 using these three functionals are longer than those (2.1–2.3 Å) reported in X-ray crystal studies of Mn­(III) porphyrins. The Mn–OH 2 distance using ωB97xD is close to that using the BP86 functional but ∼0.2 Å shorter than that using the B3LYP, probably because of the dispersion effect. The calculated MnO bond length becomes shorter in the order of 1 , 2 , and 3 in the calculations using all of these three functionals because of the trans influence of the axial ligand.…”
Section: Results and Discussionmentioning
confidence: 69%
“…15 Upon reaction with hydroxylamine, 1a undergoes reductive nitrosylation to yield the complex [Mn(TMPP 2− )(NO)], 1 . 15 Kubiak et al reported a five-coordinated nitrosyl complex of Mn( ii )–porphyrinate with {Mn(NO)} 6 configuration, which then was synthesized by bubbling excess NO gas through a CH 3 OH solution of complex 1a in the presence of NaBH 4 . 16 Complex 1 shows FT-IR stretching frequency at around 1755 cm −1 in KBr, which matches with the reported one.…”
Section: Resultsmentioning
confidence: 99%